2015
DOI: 10.1111/eos.12221
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of clonality and serotypes of Streptococcus mutans among children by multilocus sequence typing

Abstract: Studies using multilocus sequence typing (MLST) have demonstrated that Streptococcus mutans isolates are genetically diverse. Our laboratory previously demonstrated clonality of S. mutans using MLST but could not discount the possibility of sampling bias. In this study, the clonality of randomly selected S. mutans plaque isolates from African American children was examined using MLST. Serotype and presence of collagen-binding proteins (CBP) cnm/cbm were also assessed. One hundred S. mutans isolates were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…This finding indicates that these strains have identical housekeeping genes but differ within the repetitive extragenic elements. This finding offers more support of the recent report that rep-PCR can be more discriminative than MLST in some cases when evaluating S. mutans (Momeni, Whiddon, Cheon, Moser and Childers, 2015). It should also be noted that one of the previous library genotypes (L16) was reassigned to L23 due to similarities in rep-PCR profiles.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This finding indicates that these strains have identical housekeeping genes but differ within the repetitive extragenic elements. This finding offers more support of the recent report that rep-PCR can be more discriminative than MLST in some cases when evaluating S. mutans (Momeni, Whiddon, Cheon, Moser and Childers, 2015). It should also be noted that one of the previous library genotypes (L16) was reassigned to L23 due to similarities in rep-PCR profiles.…”
Section: Discussionsupporting
confidence: 84%
“…Genotypes were determined using a three minor or 1 major band difference guideline. Percent similarity was not used for determining genotypes as percent similarity becomes increasing unreliable when larger numbers of isolates are analyzed (Momeni et al, 2015). Major and minor bands were differentiated using a cut-off of 100 fluorescence units.…”
Section: Methodsmentioning
confidence: 99%
“…Serotype k is typically reported as representing less than 5% of S mutans isolates . Our laboratory previously reported the first detection of serotype k in a United States population at a notably high prevalence of 17.5% from a random selection of S mutans isolates . These findings suggested that the prevalence of serotype k in this population would be higher if biofilms (ie plaque) and saliva were evaluated instead of individual isolates.…”
Section: Discussionmentioning
confidence: 83%
“…Three sequence types were shared among multiple individuals within different families. ST119 (Thailand), ST132 (Thailand), and ST92 (Japan) were isolates matching strains identified in published studies from other countries, while all other isolates were unique to the Uniontown population (United States) [11,39,16,40,17].…”
Section: Resultsmentioning
confidence: 61%